Irradiation Effect of Argon Ion on Interfacial Structure Fe(2nm)/Si(tsi=0.5-2 nm) Multilayer thin Film - S. Purwanto (PPIKSN-BATAN, 2010)
Investigation includes formation of interfacial structure of Fe(2nm)/Si(tSi= 0.5-2 nm) multilayer thin film and the behavior of antiferromagnetic coupling between Fe layers due to Argon ion irradiation was investigated. [Fe(2nm)/Si]30 multilayers (MLs) with a thickness of Si spacer 0.5 - 2 nanometer were prepared on n-type (100) Si substrate by the helicon plasma sputtering method. Irradiation were performed using 400keV Ar ion to investigate the behavior of magnetic properties of the Fe/Si MLs. The magnetization measurements of Fe/Si MLs after 400keV Ar ion irradiation show the degradation of antiferromagnetic behavior of Fe layers depend on the ion doses. The Magnetoresistance (MR) measurements using by Four Point Probe (FPP) method also confirm that MR ratio decrease after ion irradiation. X-ray diffraction (XRD) patterns indicate that the intensity of a satellite peak induced by a superlattice structure does not change within the range of ion dose. These results imply that the surface of interface structures after ion irradiation become rough although the layer structures are maintained. Therefore, it is considered that the MR properties of Fe/Si MLs also are due to the metallic superlattice structures such as Fe/Cr and Co/Cu MLs.Received: 2 April 2009; Revised: 2 September 2009; Accepted: 5 January 2010